Analisis Pengaruh Bid Ask Spread, Market Value dan Earning Per Share Terhadap Holding Period Saham Perusahaan LQ45 di Bursa Efek Indonesia - Ima Andriyani; Djatmiko Noviantoro; Dhesy Kurniawati (Jurnal Aplikasi Manajemen dan Bisnis, 2021)
This study aims to determine and prove the effect of bid-ask spread, market value, and earnings per share on the holding period of LQ45 company shares on the Indonesia Stock Exchange. The population in this study were companies listed on the LQ45 Index from 2017 to 2019. A sample of 30 companies with a total of 90 data was determined by purposive sampling technique. The analysis technique used in this research is multiple linear regression. The data used in this study are closing price, number of outstanding shares, stock trading volume, and bid and ask prices. The results of the Adjusted R2 study indicate that holding period variations can be explained by three variables, namely bid-ask spread, market value and earnings per share. The results of the t test show that the bid-ask spread variable has a positive and significant effect on the holding period, market value has a negative and insignificant effect and earnings per share has a negative and significant effect on the holding period. The three results have been tested with a significance of = 5% and the most influential on the holding period is earnings per share. From the results of the F test, there is evidence that the bid-ask spread, market value and earnings per share simultaneously have an effect on the holding period of the stock.